Identifying isoniazid resistance markers to guide inclusion of high-dose isoniazid in tuberculosis treatment regimens. (October 2020) - Rivière, E.; Whitfield, M.G.; Nelen, J.; Heupink, T.H.; Van Rie, A.
Abstract: Objectives: Effective use of antibiotics is critical to control the global tuberculosis pandemic. High-dose isoniazid (INH) can be effective in the presence of low-level resistance. We performed a systematic literature review to improve our understanding of the differential impact of genomic Mycobacterium tuberculosis ( Mtb ) variants on the level of INH resistance. The following online databases were searched: PubMed, Web of Science and Embase. Articles reporting on clinical Mtb isolates with linked genotypic and phenotypic data and reporting INH resistance levels were eligible for inclusion. Methods: All genomic regions reported in the eligible studies were included in the analysis, including: katG, inhA, ahpC, oxyR-ahpC, furA, fabG1, kasA, rv1592c, iniA, iniB, iniC, rv0340, rv2242 and nat . The level of INH resistance was determined by MIC: low-level resistance was defined as 0.1–0.4 μg/mL on liquid and 0.2–1.0 μg/mL on solid media, high-level resistance as >0.4μg/mL on liquid and >1.0 μg/mL on solid media. Results: A total of 1212 records were retrieved of which 46 were included. These 46 studies reported 1697 isolates of which 21% ( n  = 362) were INH susceptible, 17% ( n  = 287) had low-level, and 62% ( n  = 1048) high-level INH resistance. Overall, 24% ( n  = 402) of isolates were reported as wild type and 76% ( n  = 1295) had ≥1 relevant genetic variant. Among 1295 isolates with ≥1 variant, 78% ( n  = 1011) had a mutation in the katG gene. Of the 867 isolates with a katG mutation in codon 315, 93% ( n  = 810) had high-level INH resistance. In contrast, only 50% ( n  = 72) of the 144 isolates with a katG variant not in the 315-position had high-level resistance. Of the 284 isolates with ≥1 relevant genetic variant and wild type katG gene, 40% ( n  = 114) had high-level INH resistance. Conclusions: Presence of a variant in the katG gene is a good marker of high-level INH resistance only if located in codon 315.